GEOLOGY OF GRAPHITE DEPOSITS OF UKRAINE AND PROSPECTS OF EXTRACTION IN MODERN CONDITIONS - Rudko, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Extraction of graphite and its use in various spheres of production and technology play a significant role in the economies of many countries. Distinctive characteristics of graphite, which is one of the most common forms of carbon in nature (good electrical conductivity, low hardness, resistance to heat and aggressive environments), are widely used by scientists in various scientific developments. After British researchers of Russian origin from the University of Manchester Andre Geim and Konstantin Novoselov published an article about properties of the first studied two-dimensional graphene crystal in the journal Science in 2004, and numerous studies of properties of the new material, the demand for graphite ore has been increasing, and, according to some forecasts, it will amount to more than $ 400 million by 2026. Natural flake graphite can be used in new technologies, such as graphene, which is now used in various scientific experiments, as well as in the production of lithium-ion batteries, fuel cells, nuclear and solar power plants. Geological conditions of the Zavallivske graphite deposit, which is the main source of graphite in Ukraine, have been briefly presented in the paper, and perspectives of identified areas that can become an additional reserve of graphite ore have been outlined. Significant prognosis resources of graphite in new deposits, which have been recently discovered in Ukraine (Burtynske, Balakhivske, Sachkinsko-Troitske, a number of new sites within the Zavallia area), allow not only to maintain at the appropriate level, but also, if necessary, expand existing mineral raw material base, so Ukraine could become one of the world's largest suppliers of graphite products. Graphene has a great mechanical strength and a very high thermal conductivity. An extremely high mobility of electrons makes graphene a perspective material for the application in various fields, in particular, as a future basis for nanoelectronics and possible replacement of silicon in integrated circuits. Results on the application of unique properties of graphene have been presented.
Keywords: graphite; graphite deposits; Zavalyevskiy deposit; graphene